Oxcarbazepine induces mitotic catastrophe and apoptosis in NRK-52E proximal tubular cells. (10th October 2021) - Ota, Momoka; Funakoshi, Takeshi; Aki, Toshihiko; Unuma, Kana; Uemura, Koichi
Highlights: Oxcarbazepine induces concentration dependent cytotoxicity in NRK-52E proximal tubular cells. Oxcarbazepine induces cell cycle arrest at the mitotic phase. Oxcarbazepine disrupts the activation of PLK1 to result in the formation of a monopolar spindle. Abstract: Certain medicines including anticancer drugs, NSAIDs and antiepileptic drugs are known to cause drug-induced nephropathy. For example, antiepileptic drugs such as carbamazepine (CBZ) and valproic acid have been reported to cause damage to the proximal tubular cells. Although there has been a great deal of research concerning the nephrotoxicity of CBZ, little is known about that of oxcarbazepine (OXC), a derivative of CBZ. To investigate the molecular mechanism underlying renal proximal tubular cell death caused by OXC, we examined alterations in the gene expression profile of NRK-52E proximal tubular cells during OXC exposure. DNA microarray analysis revealed that the levels of genes related to mitotic processes including chromosomal and cytoplasmic segregation, progression to G2/M phase, and formation of the mitotic spindle are increased after exposure to 50 μM OXC for 6 h. Cell cycle analysis by flow cytometry showed that OXC at concentrations between 25 and 100 μM induces G2/M arrest. We also found that OXC significantly increases histone H3 phosphorylation, indicative of mitotic cells. These results imply that OXC induces cell cycle arrest at the mitotic phase. Immunofluorescence analysis showed monopolar spindles, which are formed in response to centrosome separation defects, in OXC-treated cells. We also show that OXC suppresses the phosphorylation of PLK1, which is involved not only in the activation of the kinesin family of motor proteins for centrosome separation and bipolar spindle assembly, but also in the cleavage of centrosomal proteins. Thus, our results indicate that OXC inhibits centrosome separation by reducing the activation of PLK1, which leads to the formation of an abnormal spindle and induces mitotic catastrophe and apoptosis in NRK-52E cells.